Analisis Kemampuan Intelektual dan Motivasi terhadap Kinerja Dosen - Jariah, Ainun (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2011)
Lecturer holds a strategic position in the effort to create a professional and qualified graduates that can meet the needs of professional human resources is needed components that support the performance, intellectual and motivational lecturer in the learning process. Various educational resources such as, facilities and infrastructure, cost, technology, information, students and parents of students can function well if the professors are good also has the ability to use all available resources, the results of the analysis concluded that unlicensed intellectual ability lecturer in the medium category. This intellectual ability significantly positive effect on the performance of lecturers at 66,7%. The higher intellectual abilities will be followed by an increase in faculty performance in teaching and learning. Work motivation lecturer in the high category. The motivation of this work is significantly positive effect on the performance of lecturers at 20.50%. The higher the motivation of lecturers will be followed by an increase in faculty performance in teaching and learning. Intellectual ability and motivation significantly positive effect on teacher performance that is equal to 46.76%. With the high intellectual ability and supported with high work motivation will positively impact the performance of lecturers in teaching and learning.